Observation and Characterization of Fragile Organometallic Molecules Encapsulated in Single-Wall Carbon Nanotubes. (9th June 2014) - Ogawa, Daisuke; Kitaura, Ryo; Saito, Takeshi; Aoyagi, Shinobu; Nishibori, Eiji; Sakata, Makoto; Nakamura, Tetsuya; Shinohara, Hisanori
Abstract : Thermally fragile tris(η 5 -cyclopentadienyl)erbium (ErCp3 ) molecules are encapsulated in single-wall carbon nanotubes (SWCNTs) with high yield. We realized the encapsulation of ErCp3 with high filling ratio by using high quality SWCNTs at an optimized temperature under higher vacuum. Structure determination based on high-resolution transmission electron microscope observations together with the image simulations reveals the presence of almost free rotation of each ErCp3 molecule in SWCNTs. The encapsulation is also confirmed by X-ray diffraction. Trivalent character of Er ions (i.e., Er 3+ ) is confirmed by X-ray absorption spectrum.